2020
DOI: 10.3389/fcell.2020.571258
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Improves Atrophy, Bleeding and Cognition in the Newborn Intraventricular Hemorrhage

Abstract: The germinal matrix-intraventricular hemorrhage (GM-IVH) is one of the most devastating complications of prematurity. The short-and long-term neurodevelopmental consequences after severe GM-IVH are a major concern for neonatologists. These kids are at high risk of psychomotor alterations and cerebral palsy; however, therapeutic approaches are limited. Erythropoietin (EPO) has been previously used to treat several central nervous system complications due to its role in angiogenesis, neurogenesis and as growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…This resembles observed alterations in patients, since white matter is severely affected by GM-IVH and it is also extremely sensitive to inflammation and oxidative stress [123]. Increased neutrophil infiltration [107], increased microglia and astrocyte burdens [109,111,112,125,130,142], gliosis and glial scarring are commonly observed in the periventricular area [89,125,143]. However, increased microglia burden is also observed in brain regions distant from the lesion site, such as the cortex [32,107] or the hippocampus [144], supporting an overall inflammatory response that affects the whole brain [123].…”
Section: Neuroinflammation and Microglia In Animal Models Of Gm-ivhsupporting
confidence: 56%
See 2 more Smart Citations
“…This resembles observed alterations in patients, since white matter is severely affected by GM-IVH and it is also extremely sensitive to inflammation and oxidative stress [123]. Increased neutrophil infiltration [107], increased microglia and astrocyte burdens [109,111,112,125,130,142], gliosis and glial scarring are commonly observed in the periventricular area [89,125,143]. However, increased microglia burden is also observed in brain regions distant from the lesion site, such as the cortex [32,107] or the hippocampus [144], supporting an overall inflammatory response that affects the whole brain [123].…”
Section: Neuroinflammation and Microglia In Animal Models Of Gm-ivhsupporting
confidence: 56%
“…↑ Reactive gliosis, microglia and astrocyte burdens [32,112,[141][142][143][144]. ↑ Proinflammatory cytokines [145].…”
Section: Collagenasementioning
confidence: 99%
See 1 more Smart Citation
“…In an early postnatal hyperoxia model, EPO had pro-myelinating effects and improved cognition in adolescent and adult rats ( Dewan et al, 2020 ). In a model of germinal matrix-intraventricular hemorrhage (GM-IVH) of the preterm infant, EPO restored the neuronal density, ameliorated dendritic spine loss, and reduced inflammation and small vessel bleeding, contributing to the preservation of learning and memory abilities ( Hierro-Bujalance et al, 2020 ). Recently, using a constitutively expressing transgenic mouse line, a study demonstrated that EPO stimulated the hippocampal-specific neuronal maturation and synaptogenesis early in postnatal development in mice, contributing to improved cognitive behaviors ( Khalid et al, 2021 ).…”
Section: Epo For the Ischemic Stroke Therapymentioning
confidence: 99%
“…Animal experiments have shown that erythropoietin exerts its neuroprotective effects by reducing inflammation, oxidative stress, and apoptosis and by promoting the regeneration of neuronal stem cells and blood vessels [ 16 21 ]. Erythropoietin treatment had positive effects on short- and long-term neurological outcomes in a preclinical model of IVH [ 22 ], and some observational clinical studies also showed that erythropoietin treatment may improve neurodevelopmental outcomes in preterm infants with IVH [ 10 , 23 ]. However, the use of erythropoietin remains controversial with regard to poor outcomes [ 9 ], and both the dose and the course of erythropoietin in preterm infants is uncertain [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%